Perfil sorológico e molecular de 20 parasitos e avaliação clínica de jaguatiricas (Leopardus pardalis) e cachorros-do-mato (Cerdocyon thous) em agroecossistema no Pantanal de Miranda, Brasil - Braga, Laíza de Queiroz Viana (2019)
Investigating parasites in wildlife fauna is important for understanding how they remain present in the wild as for the risks they pose to the health of their hosts, especially when they can also infect domestic animals and humans. However, just a few researches have worked involving a wide parasitic panel and the infeccion’s influence on the health of wild animals. Here, we investigated 20 parasites in carnivores through indirect (IFAT, ELISA, MAT, AAT and FAVN) and direct (molecular and parasitological) tests, selected by their pathogenic potential for wild and domestic animals and/or human. In parallel, we evaluated clinical aspects, body conditions, hematocrit and 13 biochemical parameters. For this purpose, 13 ocelots (Leopardus pardalis) and 12 crabeating fox (Cerdocyon thous) were captured in a mosaic composed by rice fields, pasture and native forest in the Pantanal of Miranda, Brazil. We detected 14 parasites: seven transmitted by ticks, four trypanosomatids, Toxoplasma gondii, Leptospira and rabie virus, of which eight showned a higher than 50% prevalence. The coinfection rate per individual oscilated between two and nine parasites. We describe the first report of Rangelia vitalli in vertebrates in the Pantanal and Crithidia mellificae in carnivores. 18 animals showed clinical and/or laboratory aspects alterations. Ocelots were more parasitized and more affected in clinical and laboratory aspects than crab-eating foxes. We highlight the Leptospira’s serum prevalence and the high titers (up to 6,400), indicating active cycle. We detected 17 serovars, being the first description of Cynopteri, Butembo and Bataviae in free-living carnivores in Brazil and Autumnalis and Copenhageni in ocelots. The most prevalent infective serovars indicate superposition with the parasite bovine cycle. We discuss Leptospira in the area from One Health’s perspective. The work results may be related to the animals continuous exposure to agrochemicals, due to its immunosuppressive effect. With the release of several compounds in Brazil in 2019, it’s imperative to expand research about their impacts on wildlife.